Biópsias endometriais seriadas em vacas Nelore (Bos taurus indicus) durante o ciclo estra - Maziero, Rosiara Rosaria Dias [UNESP]; Mattos, Maria Clara Costa [UNESP]; Teixeira, Leandro B. C.; Martin, Ian [UNESP]; Ferreira, João Carlos Pinheiro [UNESP] (My University, 2013)
Endometrial histologycal alterations were evaluated from repeated collection of uterine samples in Nelore (Bos taurus indicus) during the estrous cycle. Sixteen adult cows with a synchronized estrous cycle were used. The endometrial samples were collected in DO (day zero; ovulation day), D5 (day five), D9 (day nine) and D13 (day thirteen) of the estous cycle. Before the samples collections, we evaluated the ovary and the uterus by transrectal ultrasonography in all the animals. The mononuclear infiltrate was predominant, however their intensity wasn’t ranged throughout the estrous cycle, isn’t representing a direct consequence of the biopsies (P > 0.05). Intensity of polymorphonuclear infiltrate varied between harvests, being absent in the first and last sample (P < 0.05). So, we concluded that bovine endometrial biopsy is an adequate technique to evaluate uterine health.

Avaliaram-se as alterações histológicas endometriais consequentes da colheita repetida de fragmentos uterinos de vacas Nelore (Bos taurus indicus) durante o ciclo estral. Foram utilizadas 16 vacas, adultas, com o ciclo estral sincronizado. As amostras de endométrio foram colhidas no D0 (dia zero; dia da ovulação), D5 (dia cinco), D9 (dia nove) e D13 (dia 13) do ciclo. Durante as colheitas, foram avaliadas, pela ultrassonografia transretal, a função ovariana e a uterina de todos os animais. O infiltrado mononuclear foi predominante, porém sua intensidade não variou ao longo do ciclo estral, não caracterizando uma consequência direta das biópsias seriadas (P > 0,05). A intensidade de infiltrado polimorfonuclear variou entre as colheitas, sendo ausente na primeira e na última amostra (P < 0,05). Assim, pôde-se concluir que a biópsia endometrial em vacas é uma técnica adequada para a avaliação da higidez uterina.
Repeat endometrial biopsies in Nelore (Bos taurus indicus) cows during estrous cycle
Keywords: Biopsy; Bovine; Endometrium; Nelore; Repeat; Biópsia; Bovino; Endométrio; Nelore; Seriada